On Value Systems, Commitment and Explaining Poland in Crisis to Germans by Polish-German Writers from Berlin: Brygida Helbig-Mischewski and Emilia Smechowski - Zduniak-Wiktorowicz, Małgorzata (Porównania, 2021)
This essay discusses motivations and various strategies of artistic involvement in Polish-German relations on the part of female writers who come from Poland, write from Berlin and represent different generations of writers associated, by way of their biographies, with Germany and Poland (e.g., Brygida Helbig-Mischewski and Emilia Smechowski). Their writings, and modes of public activity that accompany them in both countries (e.g., voicing their positions in mainstream media) are closely related to a pan-European crisis of values triggered by Brexit and its aftermath.